Investigation of the Atmospheric Attenuation Factors in FSO Communication Systems Using the Taguchi Method - Pelin Demir; Güneş Yılmaz (International Journal of Optics)
In this study, Mie and Rayleigh scattering in free space optics (FSO) communication systems were investigated in terms of the atmospheric attenuation. Because of the movement of the Earth, the communication distance and surrounding gas densities are inconsistent in each region. This change leads to atmospheric attenuation and then data losses and inefficient communication in FSO occur. Therefore, the density change and distance must be calculated in each communication once the data is transmitted. In the literature, it was observed that the atmospheric attenuation is regarding some FSO communication parameters such as transmission distance, visibility, and scatter particle size distribution, the number of particles per unit volume, scatter cross-sectional area, and wavelength. Besides, in real-time communication, it is necessary to update FSO parameters simultaneously. However, this updating process for all parameter takes a long time to adapt to a new position. This paper proposes the design of the experiment method (Doe) to determine the severity of the FSO parameters. And Taguchi’s Doe method allows analyzing of FSO communication system parameters to avoid long calculation time. Results show that the proposed method helps in understanding the priorities of the parameters in FSO and reducing the updating time.